2019
DOI: 10.3390/nu11092167
|View full text |Cite
|
Sign up to set email alerts
|

Attainment Targets for Protein Intake Using Standardised, Concentrated and Individualised Neonatal Parenteral Nutrition Regimens

Abstract: Neonatal parenteral nutrition (NPN) regimens that are individualised (iNPN) or standardised concentrated NPN (scNPN) are both currently used in preterm clinical practice. Two recent trials (one iNPN and one scNPN) each compared standard (control) and high (intervention) parenteral protein and energy dosage regimens and provided data about actual protein intake. We hypothesised that scNPN regimens would achieve a higher percentage of the target parenteral protein intake than their corresponding iNPN regimens. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The PN calculation was required for each ingredient like macronutrients, micronutrients, electrolytes, mineral, fluid volume while adjusting the fluid volume in medication and feeds. Time consumed for all the calculations mentioned above was 10 minutes (5)(6)(7)(8)(9)(10)(11)(12) in the pre-implementation phase and 1 minute (0.5-4) in the post-implementation phase with a significant difference (p-value <0.0001). The time needed in minutes for order writing in pre-implementation was five minutes (3-5), and post-implementation was one minute (0-2) with a p-value of <0.0001 that was significant, as shown in Table 5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PN calculation was required for each ingredient like macronutrients, micronutrients, electrolytes, mineral, fluid volume while adjusting the fluid volume in medication and feeds. Time consumed for all the calculations mentioned above was 10 minutes (5)(6)(7)(8)(9)(10)(11)(12) in the pre-implementation phase and 1 minute (0.5-4) in the post-implementation phase with a significant difference (p-value <0.0001). The time needed in minutes for order writing in pre-implementation was five minutes (3-5), and post-implementation was one minute (0-2) with a p-value of <0.0001 that was significant, as shown in Table 5.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have reported that standardized parenteral nutrition (SPN) is relatively safe, costeffective, and provides adequate nutrition with fewer chances of errors. It provides more calories than individualized parenteral nutrition (IPN) and increases amino acid, calcium, and phosphate intake while reducing early weight loss [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, an evaluation of 2 RCTs comparing standardized PN to IPN protocols showed that a larger proportion of very preterms achieved protein targets in their first 15 days of life with MPN compared to IPN (94% vs 77%). 14 If a protocol of MPN with lipids supply can be established at the UZ Brussel, very preterms and terms would be prime candidates for these protocols. Thus, going by the numbers included in this study, 78% (113 of 145) neonates would be eligible for these protocols.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 The shorter preparation time could be a substantial benefit for clinicians, as the longer lag-time between laboratory results and IPN manufacture can lead to discrepancies in PN administration. 14 The use of MPN might even be cost-saving in neonates due to reduced processing and preparation time in newborns and thus also reducing workload for nurses and pharmacy technicians. 15 Additional benefits of MPN solutions are their long shelf life of about 2 years 16 and fewer compounding errors than IPN (<1% vs 1.7%).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that amino acids started at 2 g/kg/d are safe shortly after birth and do not cause acidosis as feared by many. [10][11][12]…”
Section: Proteinmentioning
confidence: 99%